The Co-Transport of PFAS and Cr(VI) in porous media. (January 2022) - Huang, Dandan; Khan, Naima A.; Wang, Guangcai; Carroll, Kenneth C.; Brusseau, Mark L.
Abstract: PFAS and Cr are present at some sites as co-contaminants. The objective of this research was to investigate the co-transport behavior of per- and polyfluoroalkyl substances (PFAS) and hexavalent chromium (Cr(VI)) in porous media. Miscible-displacement experiments were conducted using two soils and an aquifer sediment with different geochemical properties. Perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) were employed as model PFAS. The retardation of PFOS was decreased in the presence of Cr(VI). Conversely, the transport and retardation of PFOA was not affected by the presence of Cr(VI). The reduction of PFOS retardation caused by Cr(VI) is likely due to sorption competition for both organic-carbon and inorganic (metal-oxides and clay minerals) domains. The relative contributions of the three soil constituents to PFOS sorption and the potential for competition between PFOS and Cr(VI) is a function of the geochemical composition of the porous media (i.e., organic carbon, metal-oxides and clay minerals). The PFAS had minimal impact on the retention and transport of Cr(VI). To our knowledge, the results presented herein represent the first reported data for PFOS and Cr(VI) co-transport in porous media. The results of this study indicate that the presence of Cr(VI) has the potential to increase the migration potential of PFOS in soil and groundwater, which should be considered when characterizing electroplating facilities, leather tanning facilities, and other co-contaminated sites. Graphical abstract: Image 1 Highlights: Cr(VI) can increase the migration potential of PFOS in soil and groundwater. Cr(VI) may compete with PFOS for both organic-carbon and inorganic domains. PFOS sorption is controlled by the geochemical composition of the porous media.